Expression of γ-tocopherol methyltransferase in chloroplasts results in massive proliferation of the inner envelope membrane and decreases susceptibility to salt and metal-induced oxidative stress by reducing reactive oxygen species - Jin, Shuangxia (Plant Biotechnol J, 2014)
The γ-tocopherol methyltransferase (γ-TMT) is an important enzyme regulating synthesis of four tocopherols (α, γ, β and δ). In this report, we investigated the role of γ-TMT in regulating abiotic stress within chloroplasts. The At γ-tmt overexpressed via the tobacco chloroplast genome accumulated up to 7.7% of the total leaf protein, resulting in massive proliferation of the inner envelope membrane (IEM, up to 8 layers). Such high level expression of γ-TMT converted most of γ-tocopherol to α-tocopherol in transplastomic seeds (~10 fold higher) in the absence of abiotic stress. When grown in 400 mM NaCl, α-tocopherol content in transplastomic TMT leaves increased up to 8.2-fold and 2.4-fold higher than wild-type leaves. Likewise, under heavy metal stress α-tocopherol content in the TMT leaves increased up to 7.5-fold, twice higher than in the wild-type. Under extreme salt stress, the wild-type accumulated higher starch and total soluble sugars but TMT plants were able to regulate sugar transport. Hydrogen peroxide and superoxide content in wild-type increased up to 3-fold within 48 hours of NaCl stress when compared to TMT plants. The ion leakage from TMT leaves was significantly less than wild-type plants under abiotic stress and with less malondialdehyde, indicating lower lipid peroxidation. Taken together, these studies show that α-tocopherol plays a crucial role in the alleviation of salt and heavy metal stresses by decreasing ROS, lipid peroxidation and ion leakage, in addition to enhancing vitamin E conversion. Increased proliferation of the IEM should facilitate studies on retrograde signaling from chloroplast to the nucleus.